Stereo Camera-Based Aerial Target Geolocation in a Ground-Based Platform Environment - Amir Hilmi Bin Ahmad Azizi (Universiti Sains Islam Malaysia, 2024)
Matric: 3202568 (FKAB)-Restricted until Oct 2026